Pengembangan Buklet Pengolahan Limbah Udang Berbasis Entrepreneurship untuk Peserta Didik SMA: Development of Entrepreneurship Based Booklet on Shrimp Waste Management for High School Students - Fitria Hikmatu Inayah; Bambang Hariyadi; Muhammad Erick Sanjaya (Universitas Jambi, 2019)
Learning process that utilizes the environment as a source of learning enables the process of shaping students’ personality towards more positive atitudes, such as caring the environment, reducing pollution, and increasing students' abilities to be more creative, innovative, and have an entrepreneurial spirit. This study aims to develop learning media in the form of entrepreneurship- based booklet for shrimp waste management for high school students. This research is a development research using ADDIE model. Data obtained from questionnaires given to students and teachers. Small group trials were continued with large group trials performed on students in SMAN 1 and SMAN 2 Tanjung Jabung Barat, and 1 biology teacher at each of these schools. Prior to the trial, product validation is done by material experts and media experts. In the small group trials at SMAN 1 and SMAN 2, the responses were 84% and 81% respectively, both are in the